COMPLEX TREATMENT OF DIARRHEA IN CHILDREN - E.G. Tsimbalova ("Paediatrician" Publishers LLC, 2010)
The article presents modern data on syndrome of acute diarrhea in children, its etiology and mechanisms of development of different types of this disease, its clinical symptoms, differential diagnosis, laboratory and instrumental methods of diagnostics. Author gives review of pathogenetic treatment and opportunities of therapy with enterosorbates, taking into account etiology of diarrhea. Another chapter of the article describes opportunities and methods of oral hydration depending of extent of exicosis. Key words: acute diarrhea, children, etiology, pathogenesis, clinical symptoms, etiotropic therapy, enterosorbates, oral hydration.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):111-1116)